Keys to streaming success: A Theoretical and Practical Approach to Measuring the Impact of On-Demand Content on SVOD Platforms - Neira, Elena; Clares-Gavilán , Judith; Sánchez-Navarro, Jordi (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article delves into the concept of success concerning content released on SVOD (Subscription Video on Demand) platforms through a qualitative methodological approach. By amalgamating academic theory with prevalent industry practices, it identifies various indicators of success, both quantitative and qualitative. The article also examines the advantages and disadvantages of the data underpinning the prevailing methodological approaches in the sector: census data and sample data. The research leads to the conclusion of the suitability of a multidimensional concept of success, integrating elements of consumption, economics, temporality, and market dynamics, as a more fitting formula for capturing consumption realities in SVOD.